Periodontal disease indicators in adults with and without physical activity: a comparative analysis (Bangladesh Journal of Medical Science, 2024)
Introduction: The intriguing link between periodontal disease severity and physical activity remains largely understudied, particularly in the Saudi Arabian population. Thus, the current research was intended to ascertain the effect of physical activity on the prevalence and indicators of periodontal diseases.Materials: The cross-sectional approach with convenience sampling was applied to the recruitment of 160 adult subjects attending gymnasiums, sports clubs, malls, primary health centres, and community dental health programs. Based on IPAQ scores, the participants were split into two distinct groups: a physically active group and a physically inactive group. The two study groups were compared with one another in terms of recorded parameters. The gathered data subsequently underwent statistical processing using SPSS 20.0.Results: Of the 160 subjects, 66.87% (n = 107) had gingivitis and 33.12% (n = 53) periodontitis. A lower mean PI (1.62±0.31) was observed in the physically active group compared to the physically inactive group (6.91±1.12). The physically active group had a mean BI of 19.01±4.53 and the inactive group 69.98±9.29. For physically active and inactive groups, mean PD measurements were 2.49±0.33 mm and 4.61±0.07 mm, respectively.Physically active individuals had a significantly lower mean CAL (2.98±0.88 mm) compared to the inactive group (5.37±1.02 mm). Parametric variances between groups are statistically significant (p